Republic of Uzbekistan : Technical Assistance Report-External Sector Statistics Mission (September 30-October 11, 2010). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
The contents of this report constitute technical advice provided by the staff of the IMF to the authorities of the Republic of Uzbekistan in response to their request for technical assistance. The main objective of the mission was to assist the Central Bank of the Republic of Uzbekistan in improving the collection, processing, and dissemination of balance of payments, international investment position, and gross external debt statistical data, including improvement of the International Transactions Reporting System, as well as implementation of a medium-term program for further development. After the Republic of Uzbekistan authorities embarked on a course toward greater openness in the country, Uzbekistan made some progress in improving the production and dissemination of statistical data, but in addition to the gains that were seen, the mission noted a number of deficiencies in the External sector statistics compilation system. It is imperative to correct the methodology for calculating operations involving reinvested income for financial corporations and reflect the results obtained in the balance of payments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet